Investigation into mixing and combustion in an optical, lean, premixed, prevaporised combustor. - Harding, Stephen C. (Cranfield University, 1996)
Gaseous and particulate emissions from combustion devices are implicated in many atmospheric environmental pollution concerns. Lean, premixed, prevaporised combustion is widely regarded as the most practical technique for reducing these emissions from gas turbine combustors to levels which will not cause significant environmental impact. This technique has been proved to be capable of reducing emissions of oxides of nitrogen to ultra low levels. However, further understanding and development is necessary before LPP combustors can be reliably fitted in production gas turbines. Particular problems are flashback and autoignition in the premixer and achieving a stable, lean primary zone. This thesis details a comprehensive series of measurements made upon a realistic LPP gas turbine combustor. The measurements elucidate the important, fundamental, physical processes which govern the performance of LPP combustors whilst providing a challenging and complete data set for CFD model validation. These measurements include data on the premixer velocity field, the fuel droplet size and velocities distributions, the fuel concentration in the premixer and primary zone and the combustion temperature. This has been interpreted to provide useful information such as the location and rates of fuel-air mixing, the proportion of temporal to spatial fluctuation in fuel concentration, the premixer swirl number, the flame brush thickness and the effect on mixing and placement of fuel fraction boiling point. It has been found that for mixing multi-component fuels in a duct, the rate of mixing and physical placement will depend on the boiling fraction of the fuel. High boiling point fractions evaporate later, experience longer droplet trajectories and mix much slower when compared to lower boiling fractions.